ANALISIS PERBANDINGAN ABNORMAL RETUR, TRADING VOLUME ACTIVITY DAN HARGA SAHAM PERISTIWA IDUL FITRI PADA PERUSAHAAN LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023 - Putra, Sony Setiawan Dwi; Damayanti, Damayanti (ITB AAS Indonesia Surakarta, 2025)
This study aims to determine whether there are differences in stock returns, abnormal stock returns, and trading volume activity before and after the Eid al-Fitr event in companies listed in the LQ 45 index on the Indonesia Stock Exchange for the period 2021-2023. The sampling method used is purposive sampling, with data obtained from 20 observed companies. The parametric test used is the paired sample t-test. The results of the partial test (paired sample t-test) show no significant difference in the trading volume activity variable when comparing 7 days before and 7 days after the Eid al-Fitr event. However, the stock return and abnormal return variables show a significant difference between the 7 days before and 7 days after the Eid al-Fitr event.